The Role of Transformational Leadership in enhancing Engagement and Motivation of Millennial Employees - Bahiroh, Eloh; Ikhlas, Ramadhani (Penelitian dan Pengembangan Ilmu, 2024)
This research explores the role of emotional intelligence (EI) in increasing the effectiveness of transformational leadership (TL) in motivating and engaging millennial employees, especially in stressful work environments that demand high performance. Through a systematic literature review (SLR) approach, researchers analyzed existing literature regarding the relationship between TL, EI, motivation and engagement of millennial employees. The findings of this study indicate that EI plays an important role as a mediator in the relationship between TL and millennial employee engagement. Leaders who have high EI are able to manage emotions effectively, create a positive work environment, and increase employee motivation and engagement. The implications of these findings emphasize the need for developing EI in leadership training to improve employee well-being and organizational productivity. This research contributes to transformative leadership theory by adding dimensions of EI and offering practical recommendations for organizations in facing the challenges of stressful work environments.